Analysis of Distance Learning Through The Google Classroom Application to Improve the Quality of Islamic Education in Asy-Syukriyyah College Tangerang - Destiani Rahmawati; Mohamad Maulidin Alif Utama; Farhan Kamiluloh (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
The development of technology and information is currently growing very rapidly. So, it has changed the paradigm of society in seeking and obtaining information, which is no longer limited to newspapers, radio, and television. One area that has a significant impact on the development of this technology in education where education is a process of information and communication from educators to students that contain educational information, which has elements of educators as a source of information, media as a means of presenting ideas, ideas, and educational materials as well as the students. The distance learning process can be delivered using a variety of techniques and technologies. E-learning is perhaps the most expensive and most advanced form of distance learning, but there are other ways of delivering training that has been used with success over the years. This research uses descriptive qualitative research methods. The results of research on the analysis of distance learning through the Google classroom application for educators in ASY-SYUKRIYYAH College Tangerang are: in the process of implementing learning, educators begin by uploading PowerPoint slide materials that are already in the class group in Google classroom. The educators can ask their students to make a list of absent that students are ready to attend material giving. After that, the educator presents the material to the students. As proof that the students understand the material, the educator will upload the assignment in the assignment section in the Google classroom. Then students can collect assignments by uploading the answers in Google classroom. The Educators can immediately give grades for assignments that have been uploaded by students; they can also give praise to students if the results of the assignments are very satisfying.Â